DIAGNOSIS OF REALITY OF PROFESSIONAL REGISTERED IN REGIONAL COUNCIL OF PHYSICAL EDUCATION 6th REGION - MINAS GERAIS - BRAZIL: ACCESSION TO THE CODE OF ETHICS (Fiep Bulletin - online, 2014)
Undoubtedly, Physical Education in Brazil today, with the upcoming mega sporting events like the World Cup (2014) and Olympic Games (2016), has been a growing area and valluation, both issues related to increasing the number of companies that invest in growth, as well as vocational training, which generates increased higher education courses in Physical Education and Sport and the possible positions to be (re)created in order to allocate graduates in the labor market. However, due to the rapidly changing world, it is essential that the Institutions of: educational and regulating the Profession, and the Professional Physical Education, are continuously aligned and prepared to suit the needs arising a society that increasingly requires reliable service and quality service. For there to be control by society, it was necessary to create the CONFEF and the CREFs, in 1998 by the Brazilian Federal Government. After this date, the system CONFEF/CREFs, created the first Code of Professional Ethics. This research was conducted with Registered Professionals at the CREF6 - Minas Gerais. The purpose of this study was to ascertain the level of understanding of the Code of Ethics for Professional Physical Education in the State of Minas Gerais. The instrument used was a questionnaire sent to all registered professionals in CREF6/MG in 2012. In our result, 88.5 % of respondents know and classify how important the Code of Ethics. In this context, 24% of professionals judge their peers as not connoisseurs of the value of ethics in their profession, 30% think the professionals are technically unprepared, so doesn´t have no professional ethics, whereas 21% of respondents consider that the professional has ethics, 14% believe that the professional is indifferent to their profession, and 6% interpret the professional as corporatist.
Keywords: Ethics; Physical Education Regional Council of the State of Minas Gerais; Reality Training